Halal cosmetics supply chain- a conceptual model - Fereshteh Mohammadian; Bahman Hajipour (International Journal of Supply Chain Management, 2016)
Increasing of Muslim population around the world will build a huge Islamic market by 2030. Since the origin of most cosmetics products are non-Muslim companies, the control of Halal quality products according of Islamic standards is a big issue for Muslims. The current research goal is to determine the controller elements of Halal quality and the effects of Halal policy on the different parts of Halal cosmetic supply chain stages and players. Use of Halal policy traceability showed that with help of this system, high halal quality cosmetics can provide and attract the consumer confidence to develop these products in Islamic markets. Therefore, Halal quality assurance by different supply chain players becomes an important subject.